High-temperature anomalous Hall effect driven by frustrated spin fluctuations in the antiferromagnetic delafossite metal PdCrO 2 - Yu Tao; Pahuni Jain; Yi Zhang; Fred Tutt; Daniel Phelan; Christian Balz; Sabrina R. Hatt; Joerg Neuefeind; Stephan Rosenkranz; Benjamin A. Frandsen; Chris Leighton (Proceedings of the National Academy of Sciences, 2025)
Metallic delafossite oxides are of exceptional interest due to their ultraclean metallic transport. In the case of PdCrO 2 , this arises in a triangular-lattice antiferromagnet, creating a unique opportunity to study frustrated magnetism in a very clean metal. Here, we combine a chemical vapor transport crystal growth approach with magnetic, thermodynamic, magnetotransport, and neutron scattering measurements to elucidate the striking anomalous Hall effect (AHE) in antiferromagnetic PdCrO 2 . The unconventional AHE (with anomalous Hall conductivity ~10 5 Ω −1 cm −1 ) and a large positive magnetoresistance effect (>1,000%) are shown to exhibit complex temperature dependencies, persisting to almost seven times the Néel temperature (~250 K). These effects are directly compared to elastic neutron scattering, inelastic neutron scattering, and neutron magnetic pair distribution function data, establishing unambiguous links between anomalous magnetotransport properties and directly probed short-range spin fluctuations. The latter occur over a notably broad temperature range due to geometrical magnetic frustration. Connecting to recent experimental and theoretical developments, these findings are discussed in terms of a temperature-dependent interplay between chiral spin order and chiral spin fluctuations, significantly elucidating the high-temperature anomalous magnetotransport in such compounds.